KEMANDIRIAN EKONOMI : MENGHAPUS SYSTEM EKONOMI SUBORDINASI MEMBANGUN EKONOMI RAKYAT - Swasono, Sri Edi (Jurnal Ekonomi & Studi Pembangunan, 2004)
Our economy is not easy to build economic transformation and social transformation to change colonial economic to be national economic because of an ex-colonial law enforcement and an individualistic minded. Market mechanism have made market failure especially on keep the society‘s interest whose include under class, so It grow, disempowerment and impoverishment.Economic policy that enforce grows but it doesn’t expand an employment is not one of mindset of fundamentalism, but it had to be aware as the interest to dominate and force a national dependency